PERBANDINGAN ESTIMASI MAINTENANCE COSTING KENDARAAN OPERASIONAL PADA PT TUNASJAYA PACKINDO - Tessa Handra; Vincent Vincent (Jurnal Bina Manajemen, 2018)
Correct cost estimation for company’s tangible and intangible asset is one of the important factors in accounting for budgeting in future periods or as a source of information in decision making for the next of the object treat. PT Tunasjaya Packindo and the entire company can not be separated from the problem of this cost estimation. Based on data collected through interviews, observation, and this documentary determining the estimated cost can be processed by two methods. With the traditional costing method of processing and the activity-based costing resulted in the difference in numbers reaching until IDR143.103,-. This shows there is one method of cost estimation is potentially overcosting or undercosting. Keywords: Activity Based Costing, Traditional Costing, Maintenance, Budgeting